Design of 2D templating molecules for mixed-dimensional perovskite light-emitting diodes - Ng, Yan Fong (2020)
Recent advances in Ruddlesden–Popper (RP) perovskites have shown highly efficient light-emitting diodes (LEDs) due to the energy confinement by an energy cascade from the quasi-2D (donors) to 3D (acceptors) states. This is achieved by forming mixed-dimensional phases using 2D templating (spacer) molecules. The effect of the spacer molecular design on the efficacy of light emission is hitherto unknown, thus motivating this study into eight different spacer molecules ranging from the naphthyl to phenyl alkyl families. The phase distribution, which influences the resultant energy landscape, can simply be modulated by the choice of this spacer molecule. It was found that a high acceptor-to-donor ratio is required to achieve the best LED efficiencies. A simple absorption spectroscopy measurement can also be employed to screen potential RP systems. The findings are of significance to other halide perovskites and lay down a useful guideline to assess new spacer molecules for more efficient RP perovskite LEDs.